Efecto de dietas artificiales en la biología de adultos de chrysoperla externa (hagen, 1861) (neuroptera: chrysopidae) - Soto, José; Iannacone, José (Instituto de Ecología, A.C., 2008)
The effects of eight diets on the biology of adult of Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) were evaluated under laboratory conditions with aims at identifying effective low cost artificial diets. A standard diet with yeast extract and seven diets composed of maca (Lepidium meyenii Walpers), soybean (Glycine max (Linnaeus) Merril) and amaranth (Amaranthus caudatus Linnaeus), in the following combinations: yeast extract plus maca, yeast extract plus amaranth, yeast extract plus soybean, yeast extract plus maca plus amaranth, yeast extract plus maca plus soybean, yeast extract plus soybean plus amaranth, and yeast extract plus maca plus soybean plus amaranth were evaluated on the biology of adults of C. externa. All diets contained honeybee, pollen and water. The influence of adult diets on viability of eggs, female fecundity, pre-oviposition period, oviposition period, post- viposition period, male and female longevity during two generations of C. externa was evaluated. The eight diets tested obtained high viability of eggs under laboratory conditions. However, diets ontaining yeast extract, yeast extract plus amaranth, and soybean plus amaranth reached higher viability of eggs. Diets of yeast extract, yeast extract plus maca, yeast extract plus amaranth, and maca plus amaranth were those that obtained the highest fecundity. In general, no significant differences were found between preoviposition period, oviposition period, post-oviposition period under eight artificial diets for C. externa, but there was a tendency to be higher in second generation. Diets with yeast extract plus maca, yeast extract plus maca plus soybean plus amaranth permitted an increase of female and male´ longevity in the second generation.